POLITICAL CULTURE OF ELOQUENCE IN THE HERITAGE OF PERSIAN-TAJIK THINKERS - SAIDOVA FAZILATMO SAIDAMIROVNA (JETA (Journal of English Teaching and Applied Linguistic), 2022)
The article is devoted to one of the important problems of the political culture . During the research from the modern socio-political science assert that the culture of speech and rhetoric are one of the most important issues in the evolutionof societyIn this connection, in the works of Persian and Tajik thinkers, one can frequently find different aspects of this problem and features of the use of rhetoric. Particularly, the artistic word, which has a social content, promote to accelerate the process of change in society.